Influence of recycled plastics on the mechanical behaviour of bituminous mistures for highway surface layers - Borges Miranda, Henrique (2023)
Europe is one of the largest producers of plastics in the world, with an annual turnover of over 350 billion euros, making it a strategic industrial sector as the global consumption of plastics increases. However, plastic is nowadays considered a serious environmental problem as it represents a large share of the world’s waste generation, with Europe being one of the largest sources of plastic waste exports. Therefore, the transition to a circular economy for plastics must be driven by Europe in order not to jeopardize the economic and environmental future of the plastics sector on the continent. Thus, it is crucial to investigate the feasibility of using recycled plastics in different applications, especially in the three main end-use markets for plastics (packaging, construction and automotive). In the construction sector, the use of plastics in road and highway construction and rehabilitation is currently being investigated due to the high potential for high-value applications and high raw material consumption. However, more knowledge is needed to make recycled plastic a common solution for road surfacing. The current study was promoted by BRISA, which was ranked the most sustainable highway operator in Europe for the third time in 2021. It aims to contribute to European efforts to investigate the feasibility (ongoing study: mechanical, functional, and environmental laboratory and field evaluation) of using recycled plastic in the production of bituminous mixtures for highway pavements in Portugal, without limiting the recyclability of bituminous mixtures. The present work focuses on the influence of recycled plastics on the water sensitivity and deformation susceptibility of bituminous mixtures under load. To perform the experimental study, the following materials were used: two bituminous mixtures with different types of coarse and fine aggregates (granodiorites and granites); a bitumen (PMB 45/80-65); a filler (limestone); and five recycled plastic additives (mainly consisting of LDPE, HDPE, LLDPE and PP, which represent about 50% of the plastics produced in Europe). The results were statistically analysed together with results of other studies on the volumetric and Marshall properties of the specimens. The results show an overall improvement in resistance to permanent deformation, without a significant benefit in water resistance. However, efforts to validate performance regarding fatigue, ageing resistance, pollutant emissions during production, placement and in service pavements are ongoing. In the statistical analysis, the ratio between binder film thickness and porosity (BFT/Vv) showed a statistically significant strong correlation with the performance indicators for resistance to permanent deformation.